Analysis of bankruptcy issues at manufacturing companies, sub-sectors of cosmetics and houseappliances registered in Indonesia Stock Exchange (IDX) year 2015-2017 using Altman Z-score - Indar Khaerunnisa; Nur Anisa Rahayu (STIE Binaniaga, 2019)
This research aims to figure out the level of companies bankruptcy by applying Altman Z-Score at the manufacturing companies registered in the Indonesia Stocks Exchange. The result of the research has indicated that ZScore model is applicable to detect the company’s potential bankruptcy issues, especially manufacturing company subsectors of cosmetics and houseappliances. Altman Z-Score model has classified the companies into three categories; safe, grey area and distress. Based on the result of the research, for the companies which are in the grey area category are suggested to improve their financial performance and to use the benefit of all the assets properly to get the revenue as much as possible. However, for the companies which are in the safe category are suggested to increase their performance, especially marketing performance so that they will receive bigger amount of the revenue, nevertheless, the potential of financial distress can be minimized accordingly. Keywords: manufacturing company, financial distress, Altman Z-Score.